Personalized statin therapy: Targeting metabolic processes to modulate the therapeutic and adverse effects of statins - Zhuangqi Shi; Shuxin Han (Heliyon)
Statins are widely used for treating lipid disorders and cardiovascular diseases. However, the therapeutic efficiency and adverse effects of statins vary among different patients, which numerous clinical and epidemiological studies have attributed to genetic polymorphisms in statin-metabolizing enzymes and transport proteins. The metabolic processes of statins are relatively complex, involving spontaneous or enzyme-catalyzed interconversion between more toxic lactone metabolites and active acid forms in the liver and bloodstream, influenced by multiple factors, including the expression levels of many metabolic enzymes and transporters. Addressing the variable statin therapeutic outcomes is a pressing clinical challenge. Transcription factors and epigenetic modifications regulate the metabolic enzymes and transporters involved in statin metabolism and disposition and, therefore, hold promise as 'personalized' targets for achieving optimized statin therapy. In this review, we explore the potential for customizing therapy by targeting the metabolism of statin medications. The biochemical bases of adverse reactions to statin drugs and their correlation with polymorphisms in metabolic enzymes and transporters are summarized. Next, we mainly focus on the regulatory roles of transcription factors and epigenetic modifications in regulating the gene expression of statin biochemical machinery. The recommendations for future therapies are finally proposed by targeting the central regulatory factors of statin metabolism.